Wiedźmy i dziwadła, czyli polska droga do parytetu - KLEJDYSZ, Natalia (Przegląd Politologiczny, 2018)
The next parliamentary elections in Poland will be held on the basis of the amended elec- toral law. The changes introduced involve a quota system: the ballots are required to provide for at least 35% of women and at least 35% of men. Nearly a hundred years passed from 1918, when Polish women first won voting rights, till the President of Poland signed the so-called parity law. It would not be true, however, to say that this was a century of struggle for the equality of rights of men and women in our country. It was only after 1989 that efficient steps could be taken in this area in Poland. Therefore, the quota system that has been introduced, to be tested in practice soon, is actually the consequence of twenty years of endeavors. The advocates of such a solution consider this to be the first step towards electoral parity. Following the solutions that numerous European countries have introduced, public debate in Poland increasingly more often refers to proposals to ‘spread’ the quota system, and then parity, also to other domains, such as management or education. The opening of a serious debate on these issues will to a large extent depend on the results of the recent quota changes of the electoral law.